Effect of Statins and Aerobic Physical Exercise on Liver Function in Dyslipidemic Rats - Morphometric Study - Accioly, Marilita Falangola; Souza, Doroteia Rossi Silva; Trevizan Padulla, Susimary Aparecida [UNESP]; Camargo Filho, José Carlos Silva [UNESP]; Carmo, Edna Maria do [UNESP]; Martins, Alex Tadeu; Brandao, Antonio Carlos; Azoubel, Reinaldo (Soc Chilena Anatomia, 2013)
The present study was carried out to evaluate the effect of statins associated with physical exercise (PE) in liver cells in dyslipidemic rats through cariometry. The animals were divided into six groups: animals subjected to a hypercholesterolemic diet (HD), simvastatin, with (G1) and without (G2) physical exercise (PE); HD submitted (G3) or not (G4) to PE, and commercial food diet (F) with (G5) and without (G6) PE. Histological analysis of the liver was performed by staining the slides with hematoxylin and eosin. The cariometric study included measuring the major and minor diameters of the hepatocytes nuclei. The Shapiro-Wilk test was also performed. To determine the differences among the groups, the Kruskal-Wallis Test with Dunn's post-test were conducted. The significance level was set at 5%. No difference was found in the hepatocytes nuclei between G5 and G6. When these groups were related with G3 and G4, reduced nuclei were observed. There was no difference between G1 and G6. The comparison between G6 and G2 showed that the nuclei in G2 were smaller. No difference was detected between G5 and G1. Changes were observed in the nuclei shape in G2 in comparison to G1. Considering G2 and G3, a decrease in the size of nuclei was observed in G3. On the other hand, G2 showed changes in shape in the comparative analysis with G4. The size and shape of G1 nuclei were larger than G3 as well as changes in shape were observed when compared to G4. G4 showed smaller nuclei than G3. Therefore, F, associated or not with the practice of PE, does not alter the size and shape of the hepatocytes nuclei; HD combined with sedentarism influences changes in the morphometric parameters of hepatocytes; and the association of simvastatin and PE seems to protect the hepatocytes nuclei with regard to HD.
Keywords: Simvastatin; Exercise; Diet; Cariometry